(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper aims to clarify the Celtiberian inscription K.1.4, which in my opinion is to be read as auz kelauniku[, thus providing a new parallel to another three Celtiberian inscriptions showing the word auz. They are potter’s signatures. This one means something like “…made (this) for the family of the Celaunici”. It also offers a new reading of a votive inscription from the ancient Lusitania Scallabitana, which reads L(ARI) COVTICIVI L(ARI) COVTIOSQ(VM) LONGONAROSQ(VM). The last word must be understood as a family name of Celtic descent *longo-nāro-, perhaps meaning “(having or ruling over) warriors provided with ships”. Last, I offer an etymology for a number of Celtiberian deities, all of them from Burgos: the godname AEIODAICINO goes back to a derivative of the Celtic compound *āgyo-dago- “good in combat”. A second deity AIIORAGATO, if the reading of the long lost inscription could be confirmed, might be from *āgyo-rāgāto- “called for help in combat”. A third one BOIOGENAE clearly comes from *bogyo-genā “born out of combat”.